A Genealogy of the Wives of the American Presidents and Their First Two Generations of Descent. - Hart, Craig (McFarland & Company, Inc., Publishers, 2004)
From Martha Washington to Laura Bush, the wife of each U.S. president has found her place in history, often setting trends and doing important work for the nation. This reference work traces the lineage of all presidents' wives, arranged alphabetically from Abigail Adams to Jane Wyman. Genealogy reveals that some of the women are connected to one another through common ancestry, sometimes even through royal blood--for example, the bloodlines of Laura Bush and Abigail Adams join at King Henry II and can then be traced to King Pepin the Short, born in 714. Several others can be traced back to Ki.